Our World In Pictures: Countries Cultures, People & Places - Mills, Andrea; DK Publishing, Inc. (New York, NY : DK Publishing, 2020)
"Every country profile is packed with photos, and each nation has a full-color map detailing its main cities, landscape features, and borders, and exactly where in the world it is. At-a-glance panels provide a quick reference to all the stats, and the easy-to-read text is full of fascinating, fun facts." -- provided by publisher.
World map -- North America -- South America -- Africa -- Europe -- Asia -- Australia and Oceania -- Polar regions -- Reference.
Includes index.
Keywords: Geography -- Miscellanea -- Juvenile literature; Civilization -- Miscellanea -- Juvenile literature; Curiosities and wonders -- Juvenile literature; Voyages around the world -- Juvenile literature; Geography -- Miscellanea; Civilization -- Miscellanea; Voyages around the world; Curiosities and wonders; Civilization; Geography; Instructional and educational works; Illustrated works; Juvenile works; Trivia and miscellanea; Instructional and educational works; Trivia and miscellanea; Illustrated works